ANALISIS PEMENUHAN 8 STANDAR NASIONAL PENDIDKAN PADA SMP NEGERI DI SULAWESI SELATAN - Ratmawati, Ratmawati; Tolla, Ismail (Pascasarjana Universitas Negeri Makassar, 2018)
The purpose of this study is to assess the fulfillment of eight national education standards (SNP) at SMP Negeri in South Sulawesi. The research method used a combination of quantitative descriptive approach and qualitative approach. Qualitative descriptive approach is depiction of research results in percentage form. Qualitative approach is the depiction of research results in the form of categories. The research location covers 3 districts / cities as the sample which is determined based on the location of the region that is, the South region is represented Makassar City, the West area is Parcare City, and Southeast region, represented by Regency of Bone. samples, 2 SMPNs were chosen, each 1 SMPN accredited A and 1 SMPN accreditation B, so the number of samples is 6 SMPN. The instruments used were questionnaires developed from national education standard indicators (SNPs) equipped with documentation, and interviews. The result of data analysis shows that the percentage of compliance level of 8 national standard of education at SMP Negeri in South Sulawesi successively as follows: (1) standard content 86% or very good category, (2) standard process 88% or very good category, (3) ) the competency standard is 84% or good category, (4) standard of educator and educational staff 72% or good category, (5)) standard of facilities and infrastructure 75% or good category, (6) 90% management standard or very good category, (7) 73% financing standard or good category, and (8) 87% rating standard or very good category. Among the eight standards that include low level of engagement, one of them is the standard of educators and education personnel, especially the education personnel, namely principals, labors, and librarians are still many who have not met the standards because they do not have a certificate of competence. Suggestions for the follow-up that ownership of competency certificates for school principals, labors, and school librarians should be a priority requirement by local governments in recruitment.